INTRAOCULAR PRESSURE CHANGES DURING FOLLICULAR AND LUTEAL PHASES OF MENSTRUAL CYCLE - KISHOR KUMAR C,; RATHNAKUMAR K,; SASIKALA C, (International Journal of Pharma and Bio Sciences, 2015)
During the period of menstruation, pregnancy and menopause which may be accompanied by eye a manifestation which is disturbing nature in women. We observed the changes in intraocular pressure occurring during various phases of menstrual cycle. In this study, 50 menstruating women were studied. To study the effect of menstruation, in 50 female volunteers, IOPs were measured after every 6th day of menstrual cycle and till end of menstrual cycle. The present study showed, there was a increase in intraocular pressure in follicular phase compared to the luteal phase. There was less significant in intraocular pressure changes with BMI.